The pathological autopsy of coronavirus disease 2019 (COVID-2019) in China: a review. Issue 3 (13th June 2020) - Zhou, Baoyong; Zhao, Wei; Feng, Ruixi; Zhang, Xiaohui; Li, Xuemei; Zhou, Yang; Peng, Li; Li, Yixin; Zhang, Jinyan; Luo, Jing; Li, Lingyu; Wu, Jingxian; et al.
ABSTRACT: The coronavirus disease 2019 (COVID-2019) that emerged in Wuhan, China, has rapidly spread to many countries across all six WHO regions. However, its pathobiology remains incompletely understood and many efforts are underway to study it worldwide. To clarify its pathogenesis to some extent, it will inevitably require lots of COVID-2019-associated pathological autopsies. Pathologists from all over the world have raised concerns with pathological autopsy relating to COVID-2019. The issue of whether a person died from COVID-2019 infection or not is always an ambiguous problem in some cases,  and ongoing epidemiology from China may shed light on it. This review retrospectively summarizes the research status of pathological autopsy for COVID-2019 deaths in China, which will be important for the cause of death, prevention, control and clinical strategies of COVID-2019. Moreover, it points out several challenges at autopsy. We believe pathological studies from China enable to correlate clinical symptoms and pathological features of COVID-2019 for doctors and provide an insight into COVID-2019 disease. Abstract : COVID-2019 pathology in the lung, bronchus, heart and intestine, which was first performed in China.